THE IMPLEMENTATION OF NEW STUDENT ADMISSION SERVICE ZONING SYSTEM IN PONTIANAK: GOOD POLICY OR BAD POLICY (PARENTS PERSPECTIVE) - martin martin (Raheema, 2020)
ABSTRACT This study aims to describe the implementation and the evaluation from the parents perspective as the vital stakeholder in new students admission service PPDB zoning system in Pontianak.. This research is case study. The results of the study are it is good policy because the reasons of learners that agree with the zoning system in accordance with the purpose of the government is to bring the quality of public schools in Indonesia and move closer to the school, so that students are more safety and more save time and cost in transportation. The zoning system still needs improvement and improvement of the system so that the Government's objectives to ensure the quality of the school are in fairness. The reason parents do not agree with the zoning system is because it is worried that it can negatively affect the spirit of learning for The students of high academic ability because of the competition not as strict as the value system/final test score. Keyword: New Student Admission PPDB, Parents, Policy ABSTRAK Tulisan ini bertujuan untuk menggambarkan pelaksanaan dan evaluasi dari sudut pandang orang tua sebagai pemangku kepentingan yang penting dalam penerimaan siswa baru PPDB sistem zonasi di Pontianak. Penelitian ini adalah studi kasus. Hasil penelitian ini adalah kebijakan yang baik dalam hal system Zonasi karena pendapat dan alasan dari pelajar yang setuju dengan sistem zonasi sesuai dengan tujuan pemerintah adalah untuk membawa kualitas sekolah umum di Indonesia dan bergerak lebih dekat ke sekolah, sehingga siswa lebih aman dan lebih menghemat waktu dan biaya dalam transportasi. Sistem zonasi masih perlu perbaikan dan peningkatan sistem sehingga tujuan pemerintah untuk memastikan kualitas sekolah yang adil. Alasan orang tua tidak setuju dengan sistem zonasi adalah karena khawatir bahwa hal itu dapat berdampak negatif terhadap semangat belajar bagi siswa kemampuan akademik tinggi karena persaingan tidak seketat dengan adanya nilai ujian akhir/Skor UN. Kata kunci: pendaftaran mahasiswa baru PPDB, orang tua, kebijakan